Bulgaria’s Protection of the “Historic Communities” in the EU Enlargement Context - Dmitry I. Polyvyannyy (Современная Европа)
The article considers international activities of Bulgaria towards the Western Balkans states within the context of the EU further enlargement in 2018–2024. The author aims to evaluate the strategy of Sofia policies towards Bulgarian communities in Albania, Kosovo, Serbia and North Macedonia against the background of the internal political situation. Special attention is paid to the Presidential institution, which provides the continuity of the external policies in the situation of crisis of the political parties and parliamentarian system. Though the National Strategy towards Bulgarian citizens and Bulgarian historic communities over the world approved by the Bulgarian Government in 2014 was not further developed, the ongoing international activities of Sofia constitute a strategy of practical actions. In the bilateral relations with Albania, Kosovo and Serbia Sofia insists on constitutional guarantees of the Bulgarian historic communities’ status and rights. The inclusion of Bulgarians in the list of national minorities in the Albanian legislation serves as argument in the negotiations with the other two states. In the bilateral relations with the Republic of North Macedonia Sofia puts forward the guidance of the good neighbor principles according to the treaty on friendship, good neighborhood and cooperation signed on August 1, 2017 aligning the constitutional recognition of the Bulgarian minority with history, language and identity issues considered by special bilateral multidisciplinary commission. The activities of Bulgaria are based on its strategic evaluation of the abovementioned states’ perspectives, are being substantiated with the European legal norms, meet the support of the society and rely upon Brussel’s understanding and support.